The Biogenesis and Functions of circRNAs and Their Roles in Breast Cancer - Tang, Liting; Jiang, Baohong; Zhu, Hongbo; Gao, Ting; Zhou, Yu; Gong, Fuqiang; He, Rongfang; Xie, Liming; Li, Yuehua (Frontiers in Oncology, 2021)
Recent statistics show that breast cancer is among the most frequent cancers in clinical practice. It is also the second-leading cause of cancer-related deaths among women worldwide. CircRNAs are a new class of endogenous regulatory RNA molecules whose 5' end and 3' end are connected together to form a covalently closed single-stranded loop by back-splicing. CircRNAs present the advantages of disease-specific expression and excellent expression stability, and they can modulate gene expression at posttranscriptional and transcriptional levels. CircRNAs are abnormally expressed in a multiple cancer, such as breast cancer, and drive the initiation and progression of cancer. In this review, we describe current knowledge about the functions of circRNAs and generalize their roles in all aspects of breast cancer, such as cell proliferation, the cell cycle, apoptosis, invasion and metastasis, autophagy, angiogenesis, drug resistance, and tumor immunity, and their prognostic and diagnostic value. This may add to a better understanding of the functions and roles of circRNAs in breast cancer, which may become new diagnostic and predictive biomarkers of breast cancer.